Implications of Digital Technology for Criminal Law Enforcement: Challenges and Opportunities in the Age of Digitalization - Karina, Ica; Gultom, Maidin; Saida Flora, Henny; Sidabalok, Janus; Butarbutar, Elisabeth Nurhaini (Universitas Ekasakti, 2024)
This research aims to investigate the impact of technology and innovation on justice in law enforcement in the digital age. In the ever-evolving digital age, technological developments such as big data analytics, artificial intelligence, and digital forensics have transformed the landscape of law enforcement operations. This research outlines the positive and negative impacts of such technologies on justice in the legal system. The findings of the literature review indicate that the utilisation of technology in law enforcement has the potential to enhance the efficiency of investigations, evidence analysis, and detainee monitoring. However, there are also concerns related to the protection of privacy and the security of data that warrant consideration. Moreover, the unequal access to technology and data can pose a threat to the principles of justice. This research will enable the relevant stakeholders in law enforcement and public policy to comprehend the implications of technology and innovation for justice. Furthermore, it provides a foundation for future researchers to conduct more in-depth empirical research on these issues.